ANALISIS YURIDIS DAN SOSIOLOGIS PERLUASAN TANGGUNG JAWAB HUKUM RUMAH SAKIT DI INDONESIA: TANTANGAN DAN SOLUSI - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Jurnal Kesehatan, 2025)
The expansion of hospitals‘ legal responsibilities in Indonesia has become a crucial issue as public demands for the protection of patients’ rights in healthcare services continue to rise. This analysis explores the legal and sociological aspects related to this issue, including challenges arising from regulatory gaps, inadequate legal infrastructure, and the level of human resource competence in addressing these changes. This study also explores strategic solutions such as regulatory updates, healthcare worker training, and enhanced oversight mechanisms as steps to bridge the gap between public expectations and on-the-ground implementation. It is hoped that the findings of this research will contribute to the formulation of more equitable and responsive legal and social policies in line with the evolving healthcare system in Indonesia.